Guidelines in urology: Lights and shadows. Issue 3 (August 2020) - Cai, Tommaso; Cocci, Andrea; Gacci, Mauro; Verze, Paolo; Bonkat, Gernot; Koves, Bela; Wagenlehner, Florian; Bartoletti, Riccardo; Bjerklund Johansen, Truls E
Clinical practice guidelines have become increasingly important in the decision-making process in many clinical conditions and have been recognized as key instruments to improve the quality of care. On the one hand, guidelines represent a good tool for improving patient's outcome, and on the other hand, the adherence to guidelines and good practice recommendations is mandatory to reduce the risk of legal disputes. A recent revision by the Italian Parliament of the legal system that rules the responsibilities of health professionals and health care safety stimulated all clinicians to improve their adhesion to clinical guidelines. It is justified by the high-quality level obtained in the recent years by the international guidelines. In the recent years, a revision of the clinical guideline development has been done. In particular, the European Association of Urology Guideline Office changed the "Guidelines for Guidelines, " and a rigorous development process has been established. A clinical recommendation is produced after a rigorous methodological process using an analysis of all published clinical trials, and the expert opinion is not yet considered. For oncological guidelines, the adherence to the producing process is easily feasible due to the high number of clinical trials; for non-oncological guidelines, instead, the small number of clinical trials could represent a problem for obtaining recommendation based on rigorous methodology. Here, on the basis of these considerations, we aim to discuss the lights and the shadows of the clinical applicability of guidelines in urology.